Ex vivo T-cell depletion with the monoclonal antibody Campath-1 plus human complement effectively prevents acute graft-versus-host disease in allogeneic bone marrow transplantation. - Heit, W; Bunjes, D; Wiesneth, M; Schmeiser, T; Arnold, R; Hale, G; Waldmann, H; Heimpel, H (1986)
We have developed a rapid and simple procedure for the elimination of mature T-cells from the donor marrow using a single incubation with the monoclonal antibody Campath-1 and donor complement. This resulted in a reduction of T-cell contamination to a mean of 1%. This regimen reduced the incidence of acute graft-versus-host disease significantly in 21 consecutive bone marrow grafts in 18 patients with leukaemia and non-Hodgkin's lymphoma. Purging was responsible for an increased incidence of graft rejection in HLA-identical transplants (13%).